Dinamika Rasio BOPO dan Implikasinya terhadap Kinerja Keuangan BCA Syariah Selama Periode 2020–2024 - Asy’ari, Hilda Aulia (Maliki Interdisciplinary Journal, 2025)
This study examines the operational efficiency of Bank BCA Syariah by analyzing the Operational Expenses to Operating Income ratio (BOPO) and its implications for profitability over the period 2020–2024. Using a descriptive quantitative approach based on publicly available financial reports issued by the Financial Services Authority (OJK), this research identifies trends in BOPO and evaluates their relationship with profitability indicators. The findings reveal significant fluctuations in BOPO, with its highest increase occurring in 2022 due to rising operational expenses associated with digital transformation, employee costs, and impairment loss reserves. Improvements were observed in 2023–2024 as the bank strengthened its risk management, optimized digital services, and enhanced operational revenue. The analysis confirms a negative relationship between BOPO and profitability, indicating that higher BOPO leads to a decline in Return on Assets (ROA) and overall financial performance. This study highlights the importance of operational efficiency as a strategic determinant of sustainable profitability and competitiveness for Islamic banks, particularly in the context of rapid digital and industrial transformation.